THE EFFECT OF LIQUIDITY RATIOS AND RATIO OF RENTABILITY TO SOLVABILITY RATIOS. (Empirical Study of Plactics and Packaging Sub Sector Companies Listed on the Indonesia Stock Exchange in 2015-2019) - Fritz Dholly Hutapea; Paul Eduard Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2020)
The purpose of this study are to determine the impact of the liquidity ratio represented by the current ratio and the rentability ratio represented by the gross profit margin ratio on the solvability ratio represented by the debt to equity ratio. The research method is descriptive with quantitative approach. This research was conducted upon plastic and packaging companies listed in Indonesian Stock Exchange in 2015 to 2019, with the number of samples is 8 companies in accordance with the criteria esthablised by the author. The result show all the companies have a good current ratio and gross profit ratio and the companies has a small debt to equity ratio. In the partial test it was found that the current ratio dan gross profit margin ratio had no significant on the debt to equity ratio, in simultaneous test of current ratio and gross profit ratio has a significant relationship to debt to equity ratio.